THE AIMS AND TASKS OF THE FORMATION OF FOREIGN LANGUAGE COMMUNICATION COMPETENCE OF THE PRIMARY COMPREHENSIVE SCHOOL PUPILS ON THE ADAPTIVE STAGE OF TEACHING A FOREIGN LANGUAGE - Олена Паршикова (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article is devoted to the development of theoretical foundations, particularly the aims and tasks of teaching a foreign language to primary comprehensive school pupils. According to the research teaching a foreign language in the primary comprehensive school consists of two stages: the first adaptive stage with the sub-stages of phonological and lexical-semantic adaptation and the second, reorganizational stage with the sub-stages of syntactical and morphological reorganization. The aim of the first stage of teaching a foreign language to primary comprehensive school pupils lies in the formation of their elementary foreign language communication competence on the level A1.1, which includes levels A1.1.1 and A1.1.2. The objects and aims of teaching a foreign language: quasicommunication on level A1.1.1 and protocommunication on level A1.1.2 are determined and characterized, the priority tasks of formation of all components of foreign language communication competence are amplified in correspondence with the processes of foreign language acquisition by juniors, as well as their age abilities in their dynamic development.